2021
DOI: 10.18632/oncotarget.28041
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of Prolyl oligopeptidase (POP) inhibition in acute lung injury induced by intestinal ischemia-reperfusion

Abstract: Intestinal ischemia-reperfusion (II/R) develops when the blood flow to the intestines decreases, followed by the reestablishment of the blood supply to the ischemic tissue, resulting in intestinal mucosal barrier dysfunction, with consequent severe local and systemic inflammation. Acute lung injury (ALI) represents the most serious complication after II/R. KYP-2047 is a selective inhibitor of prolyl oligopeptidase (POP), a serine protease involved in the release of pro-angiogenic and inflammatory molecules. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The POP-associated production of the collagen-derived neutrophil chemoattractant PGP and the self-sustaining neutrophil-driven constant inflammation linked the enzyme to various inflammatory pulmonary conditions, such as COPD and cystic fibrosis [ 18 ]. Previous studies have demonstrated the involvement of POP in inflammation, angiogenesis, oxidative stress and apoptosis, so POP inhibition could be a potential target in order to counteract lung injury [ 15 ]. A number of POP inhibitors, such as the selective inhibitor of POP, KYP-2047 (4-phenyl-butanoyl-l-prolyl-2(S)-cyanopyrrolidine) and valproic acid, have been developed and extensively studied in various in vitro and in vivo models of inflammatory diseases with beneficial effects against these mechanisms that the POP enzyme is involved [ 15 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The POP-associated production of the collagen-derived neutrophil chemoattractant PGP and the self-sustaining neutrophil-driven constant inflammation linked the enzyme to various inflammatory pulmonary conditions, such as COPD and cystic fibrosis [ 18 ]. Previous studies have demonstrated the involvement of POP in inflammation, angiogenesis, oxidative stress and apoptosis, so POP inhibition could be a potential target in order to counteract lung injury [ 15 ]. A number of POP inhibitors, such as the selective inhibitor of POP, KYP-2047 (4-phenyl-butanoyl-l-prolyl-2(S)-cyanopyrrolidine) and valproic acid, have been developed and extensively studied in various in vitro and in vivo models of inflammatory diseases with beneficial effects against these mechanisms that the POP enzyme is involved [ 15 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the involvement of the cleaving enzyme prolyl oligopeptidase/endopeptidase (POP/PREP) in ALI [ 15 ]. The pro-inflammatory nature of POP is attributed to its ability to generate the neutrophil chemoattractant matrikine proline-glycine-proline (PGP) from collagen fragments [ 16 ] with the concerted action of metalloproteinases.…”
Section: Introductionmentioning
confidence: 99%
“…Hind paw and lumbar spinal cord tissue sections were processed for immunohistochemical analysis, as previously described [ 23 ]. Sections were incubated overnight with: IL-1β (sc-12742, 1:100), scaffolding protein postsynaptic density protein-95 (PSD95) (sc-32291, 1:100) and anti-NMDAε2 (NR2B) (sc-365597, 1:100).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of fibrosis of the renal sections was assessed using Masson’s trichrome stain, following the manufacturer’s instructions (Bio-Optica, Milan, Italy), as previously described [ 73 , 74 ]. This staining allows highlighting connective tissue, collagen, reticular fibers, and muscle fibers.…”
Section: Methodsmentioning
confidence: 99%